Israeli mental health in the aftermath of the October 7 terrorist attack: risks, challenges, and recommendations - Yuval Neria; John C. Markowitz; Doron Amsalem; Yossi Levi-Belz; David Roe; Ido Lurie; Dana Tzur Bitan; Milton L. Wainberg; Shlomo Mendlovic (Israel Journal of Health Policy Research)
Abstract Background The October 7, 2023 terrorist attack and subsequent war in Israel have created an unprecedented mental health crisis. This commentary examines emerging data on the psychological impact of these events and argues for a paradigm shift in the Israeli mental healthcare system. Main body Recent studies reveal a dramatic increase in PTSD, depression, and anxiety among the Israeli populace. These findings underscore the long-lasting and pervasive nature of psychological trauma. Certain populations are disproportionately affected: women, ethnic minorities (particularly Israeli Arabs, who comprise 18.1% of the population), and those experiencing traumatic loss, displacement, or economic hardship. These groups require prioritized and tailored interventions. While existing outcome research provides a solid foundation for treating common trauma-related disorders like PTSD, depression, and anxiety, the Israeli mental health system is ill-equipped to handle the surge in demand. Too many clinicians lack training in evidence-based trauma therapies and standardized assessments. To address this gap, we advocate a system-wide transformation. This involves widespread training in evidence-based assessments and time- limited therapies, a focus on precision psychiatry tailored to individual needs, and the implementation of task-shifting and task-sharing models to expand access to care. Conclusion These strategies are crucial for mitigating the long-term mental health consequences of the October 7th attacks and fostering individual and societal resilience. Failure to act decisively will exacerbate the existing crisis, placing further strain on individuals, families, and Israeli society as a whole.